2018
DOI: 10.1089/aid.2018.0126
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Complexities Among Patients with Tuberculosis in a High HIV Prevalence Cohort in the United States

Abstract: The association between human immunodeficiency virus (HIV) infection and tuberculosis (TB) mortality has been studied extensively, but the impact of HIV on other clinically relevant aspects of TB care such as TB drug-related adverse events (AEs), hospital readmissions, and TB treatment duration is less well characterized. We describe the association of HIV infection with TB clinical complexities and outcomes in a high HIV prevalence cohort in the United States. This is a retrospective cohort study among patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…This is in keeping with a systematic review done in the European Union which reported that the majority of HIV-TB co-infected cases were male and young adults, aged between 25-45 years (15). We also found that the prevalence of diabetes mellitus (DM) in our cohort was 12% which was similar to a study conducted by Bizune et al in the United States, which reported a prevalence of 9% (16). The high proportion can be explained by diabetes predisposing to TB and ART increasing the risk of metabolic syndrome and thus predisposing to DM (17), and also underscores the increase in DM prevalence in developed countries.…”
Section: Discussionsupporting
confidence: 91%
“…This is in keeping with a systematic review done in the European Union which reported that the majority of HIV-TB co-infected cases were male and young adults, aged between 25-45 years (15). We also found that the prevalence of diabetes mellitus (DM) in our cohort was 12% which was similar to a study conducted by Bizune et al in the United States, which reported a prevalence of 9% (16). The high proportion can be explained by diabetes predisposing to TB and ART increasing the risk of metabolic syndrome and thus predisposing to DM (17), and also underscores the increase in DM prevalence in developed countries.…”
Section: Discussionsupporting
confidence: 91%
“…Based on a previous study, male sex has other predictors of non-compliance to TB treatment, for example, smoking history and drug abuse [21], while women have higher accessibility to TB care than men [22]. Treatment complexity is a primary consideration of poor compliance in TB/HIV coinfection [23,24]. Improvement in TB care in HIV patients could be achieved through mentoring and training programmes [25].…”
Section: Discussionmentioning
confidence: 99%
“…Por conseguinte, na análise multivariada, a coinfecção pelo HIV apresentou a mesma Resultados de coorte realizada nos Estados Unidos, na qual utilizou modelagem de regressão logística para estimar a associação do HIV com desfechos desfavoráveis do tratamento da TB, também encontrou uma maior tendência de desfechos desfavoráveis em casos de coinfecção TB-HIV, contudo não mostrou associação estatisticamente significativa. Apesar disso, os pacientes coinfectados tiveram um curso de tratamento mais complexo (Bizune;.…”
Section: Discussionunclassified